KAJIAN STRUKTUR DAN KOMPOSISI VEGETASI MANGROVE DI KAWASAN PESISIR DESA PASAR BANGGI, KABUPATEN REMBANG - Saputro, Irawan; Pribadi, Rudhi; Pratikto, Ibnu (977-2407769)
The condition of an ecosystem mangrove in the Pasar Banggi appertain one of the best in northern coast in central java. Management mangrove ecosystem there begin since the 1960s with conduct rehabilitation especially independently by the community. This condition, is perceived as a good condition and could be a good example to be applied in other areas. The purpose of this study is to know about the structure and composition of mangrove vegetation in Coastal Pasar Banggi Village, Rembang District. Vegetation data taking based on purposive sampling method and every transect made sampling plot. Each tree (plot 10 m x 10 m) and sapling (subplot 5 m x 5 m) identified and measured on diameter at breast height (± 1.3 m). Seedling calculated the amount of each species and the percentage of cover on subplot 1 m x 1 m. The result of research in Pasar Banggi Village was found 11 mangrove species. Generally, tree mangrove in Pasar Banggi Village have the range of density 100 ind/ha – 2533 ind/ha which dominated by Rhizophora mucronata. The Index of diversity (H’) and Eveness (J’) of mangrove vegetation in Coastal Pasar Banggi Village, Rembang District, were in low category.